(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article contains the results of the study of terpenoid coumarins of the Ferula Conocaula plant growing in the pastures of the Osh region. This plant species is widespread in the Alai mountain range. Since ancient times, it has been widely used in folk medicine: for the treatment of nervous, skin, dental, gastrointestinal diseases. In modern medicine: substances isolated from this plant and powders, emulsions, tinctures are used for flatulence, tremors, nervous diseases, gynecology, as expectorants, etc. There is no data on the study of the chemical composition of the Ferula Conocaula plant growing in Kyrgyzstan. Therefore, we began to study the coumarin composition of the roots of this plant grown in the Kara-Tash pasture of the Osh region, located at the foot of the Alai mountain range, excavated after vegetation. As a result, four substances belonging to terpenoid coumarins were isolated, the physicochemical properties of one of them were studied, and it was identified with the substance ferrocholine, previously isolated from this plant growing in the flora of Tajikistan. The study of the chemical composition of the plant Ferula Conocaula continues.